Evaluation of educational environment among MBBS students in a medical college from Central India - Barela, Shamvel; Padyal, Pratik; Ukey, Ujwala; Narlawar, Uday; Bembade, Shubhangi; Krishnan, Ajaya; Gopi, Akash; Kumar, Mohit; Deotale, Vipul; Shegokar, Priyanka (International Journal Of Community Medicine And Public Health, 2025)
Background: The educational environment plays a vital role in shaping the learning experiences, academic performance, and well-being of medical students. Evaluating students' perceptions helps identify strengths and gaps within the existing system and offers opportunities for improvement. The objective as to assess the perception of the educational environment among MBBS students in a medical college in Central India using the DREEM-12 (Dundee Ready Education Environment Measure) questionnaire. Methods: A descriptive cross-sectional study was conducted among MBBS students at a tertiary healthcare center in Central India over a period of two months, from November to December 2024. A total of 492 students participated in the study through convenience sampling. The DREEM-12 questionnaire, consisting of 12 items across five subscales, was used to evaluate students’ perceptions of learning, teachers, academic self-perception, atmosphere, and social self-perception. Each item was scored on a 5-point Likert scale, with a maximum possible score of 48. Results: The overall mean DREEM-12 score was 30.92 out of 48, reflecting a generally positive perception of the educational environment. Subscale scores indicated favourable perceptions in students’ learning (5.6), perception of teachers (8.2), academic self-perception (7.5), and perception of atmosphere (5.0). The lowest score was in social self-perception (4.63), highlighting the need for better stress management and social support systems. Conclusions: The study revealed that MBBS students have an overall positive perception of their educational environment. However, targeted efforts to enhance social support and student well-being are essential to further improve the academic experience.